Fantasies of Empire : the Empire Theatre of Varieties and the licensing controversy of 1894 - Donohue, Joseph W., Jr. (Joseph Walter), 1935- (Studies in theatre history and culture., 2005)
In the London summer of 1894, members of the National Vigilance Society, led by the well-known social reformer Laura Ormiston Chant, confronted the Empire Theatre of Varieties, Leicester Square, and its brilliant manager George Edwardes as he applied for a routine license renewal. On grounds that the Empire's promenade was the nightly resort of prostitutes, that the costumes in the theatre's ballets were grossly indecent, and that the moral health of the nation was imperiled, Chant demanded that the London County Council either deny the theatre its license or require radical changes in the Emp.